Lesiones histopatológicas más frecuentes en el endometrio de perras clínicamente sanas en diestro - Praderio, R.G. (2018)
Infertility and subfertility are common problems in small animal reproduction. In the last years some studies suggested that subclinical endometritis (SE) could be an important cause of infertility/subfertility. The aim was to study the endometrium in healthy bitches. Seventy nine bitches, clinically healthy, aged between eight months and six years old, in diestrous, have been included in this work. Bitches were divided in 3 groups G1: bitches treated with progestins (n=8), G2: bitches never treated with progestins (n=49), G3: bitches without data about the use of progestins (n=22). The dioestrus was determined based on the date of the last heat, the study of vaginal cytology and the presence of corpus luteous in ovary. A biopsy was obtained from each uterine horn, placed in 10% (pH 7.0/7.4) buffered formalin solution and processing for histopathology study. Samples were observed with an optical microscope at 4X, 10X, 40X and 60X. Twenty two bitches showed normal endometrium, 47 showed SE, 7 showed cystic endometrial hyperplasia and three bitches had other conditions. Our results suggest SE could be an important cause of infertility/subfertility in the bitch.